Análise do custo do diagnóstico laboratorial da tuberculose pulmonar e investigação do Mycobacterium tuberculosis da sublinhagem RDRio no estado de Minas Gerais - Isabela Neves de Almeida (2017)
Background: At a global level, with the increase in healthcare costs, there is a need to assess the economic impact of the incorporation of new technologies in different health disorders in different countries. There is scarce information regarding costs incurred with the use of current or new diagnostic tests for tuberculosis or from the vantage point of their incorporation within the healthcare systems of high-burden countries. The present study aimed to assess the mean cost and the activity based cost of the laboratory diagnosis for tuberculosis by means of conventional techniques and from the Detect TB®LabTest molecular test kit in a general high-complexity hospital of the public health system in Brazil. Methods: Cost analysis was performed by means of primary data, collected in the Mycobacteria and Molecular Biology Laboratory in 2013. Results: The mean cost and activity based cost were, respectively, U$10.06/U$5.61 for centrifuged bacilloscopy by Ziehl Neelsen and Auramine; U$7.42/U$4.15 for direct bacilloscopy by Ziehl Neelsen; U$27.38/U$16.50 for culture in a Loweinstein-Jensen solid medium; and U$115.74/U$73.46 for the Detect TB®LabTest Kit. Conclusions: The calculation of the ABC should be used in making decisions by administrators to be the best method of assessing the costs of conventional techniques and molecular method for providing the real value of the tests. So it is need to calculate the ABC, and not of the mean cost, in various scenarios before incorporating new technologies in health institutions.